Comparative Study of Glycemic Status of Very Low Birth Weight Neonate Treated with 10% Dextrose Versus 05% Dextrose (Sir Salimullah Medical College Journal, 2022)
Background: Low birth weight and preterm birth account for major public health problems in developing countries (including Bangladesh) and are major determinants of public health status. Metabolic complication of low birth weight neonate is common including hypoglycemia as well as hyperglycemia. Both of which is associated with short term mortality and long-term morbidity.Objectives: The objective of this study was to compare the glycemic status of very low birth weight neonate when treated with 10% dextrose and 5% dextrose.Methods: The study was conducted in Department of Pediatrics in Shahid Ziaur Rahman Medical College Hospital, Bogra. Study period was from march 2016 to august 2016. Neonates were divided into two groups, group 1 received 10% dextrose and group 2 received 5% dextrose. Baseline blood glucose and six hourly blood glucose monitored. Total five blood glucose value including one baseline value were taken from each neonate to compare the effect of blood glucose on dextrose infusion in between two group. Total 60 patients were included in the study.Result: Baseline blood sugar were within normal ranges between 2.5 to 7.0 mmol/ l. At 6, 12, 18- and 24-hour hyperglycemia develop in 21(58.3%), 19(52.8%),15(41.7%) and 12(33.3%) of patient in 10% dextrose group respectively. In 5% dextrose group corresponding number is 6(25%),5(20,8%),2(8.3%) and 2(8.3%) at 6, 12,18 and 24 hours respectively. The difference between two group is statistically significant (p